Clinical effectiveness of bevacizumab in patients with recurrent brain tumours: A population-based evaluation. (January 2018) - de Lemos, Mário L; Markarian, Adeline; Chan, Esther; Schaff, Kimberly; Walisser, Susan
Background: Bevacizumab is an antiangiogenic agent active in patients with recurrent malignant gliomas. However, evidence for its clinical efficacy is relatively limited so that bevacizumab is approved for this indication in Canada and the United States, but not in the European Union. We reviewed the effectiveness of bevacizumab in patients with recurrent brain tumour using a large population database. Methods: This was a retrospective, multicentre, study conducted at the BC Cancer Agency, a public cancer care organisation for the residents of the Canadian province of British Columbia. Cases were identified from the provincial registry and drug database. Patients were eligible if they were treated with bevacizumab with or without lomustine or etoposide for recurrent brain tumour between April 2011 and March 2014. The primary end points were progression-free survival. Secondary endpoints were overall survival and objective response rate. Results: A total of 160 patients were included, with a median age of 55 years. The most common diagnosis was glioblastoma multiforme (70.6%), followed by oligodendroglioma (10.6%). Half of the patients had prior metronomic dosing of temozolomide. The median duration of therapy was 3 months. The median progression-free survival was 4.0 months and the 6-month progression-free survival was 29.4%. The median overall survival was 7 months and the 9-month and 12-month overall survival was 28.1% and 20.6%, respectively. The objective response rate was 23.1%. The most common documented reason for bevacizumab discontinuation was disease progression (66.9%), followed by toxicity (6.9%). Conclusions: Bevacizumab therapy seems to be effective in delaying disease progression in patients with recurrent brain tumour, but with limited benefits on the overall survival, when used outside the clinical trial setting.